2022
DOI: 10.9734/jpri/2022/v34i15b35718
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation Study of Glimepiride: An Insight for Formulation and Development of Parenteral Formulation

Abstract: Aim: The objective of preformulation study is to develop the elegant, stable, effective and safe dosage form by establishing kinetic profile, compatibility with other formulation excipients and physico-chemical parameters of new drug substance. This could provide important information for formulation design or support the need for molecular modification. So, in the present study preformulation studies were performed on Glimepiride (GMP) to assess its suitability for parenteral formulation. Glimepiride is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The absorption maxima was obtained to be 224.0 nm and was used to measuring the absorbance of glimepiride in solutions throughout the study. In previous studies the absorption maxima have been reported to be 225 nm 50 , 228 nm 57 and 236 nm 58 .…”
Section: Uv Absorption Spectra Of Glimepiridementioning
confidence: 82%
“…The absorption maxima was obtained to be 224.0 nm and was used to measuring the absorbance of glimepiride in solutions throughout the study. In previous studies the absorption maxima have been reported to be 225 nm 50 , 228 nm 57 and 236 nm 58 .…”
Section: Uv Absorption Spectra Of Glimepiridementioning
confidence: 82%
“…This indicated that glimepiride is a crystalline material that melts sharply upon heating. Table 3 presents data on thermal transitions, melting points, and thermal degradations of drug, PVP K-90, PVA, and Soluplus ® [ 27 ]. The physical mixture of glimepiride and its excipients exhibited a noticeable shift in the melting point, indicating enhanced thermal stability and preventing drug degradation at 205 °C, as evident from the thermogram illustrated in above Figure 9 b.…”
Section: Resultsmentioning
confidence: 99%
“…Two mg GM was mixed with each of the components (PVA, PVP, and Soluplus ® ) at an appropriate ratio, equivalent to that used in the formulation. The spectra of the pure GM, Soluplus ® , PVA, and PVP K-90 and their physical mixture were analyzed by scanning across a frequency span ranging from 4000–400 cm −1 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The moisture uptake measurement is done by Karl Fischer titration, Thermogravimetric analysis (TGA), and gas chromatography techniques. As per European Pharmacopoeia, four separate grades of hygroscopicity are defined when a drug substance is stored at 80% relative humidity and a temperature of 25°C for 24 h. The four classes of hygroscopicity are described here as per the above-mentioned storage conditions [48,49].…”
Section: Hygroscopicity and Deliquescencementioning
confidence: 99%
“…The active metabolite hydrocortisone is produced when prednisolone and cortisone are reduced. Azo dyes are used as colouring additives in drug products or food items and this can be degraded by liver and intestinal flora to create amines [48].…”
Section: Reductionmentioning
confidence: 99%